HUBUNGAN KEGIATAN KULIAH TUJUH MENIT DENGAN KOMUNIKASI SISWA DI MTsN 1 BUKITTINGGI - Erin Angriani; Charles, Salmiwati, Nurhasna (Jurnal Komunikasi, 2025)
The background to this research is that MTsN 1 Bukittinggi routinely holds cult activities on Fridays once a month. The performance system is left to student creativity. In terms of the influence of implementing cult activities on student communication, sometimes students lack self-confidence so they are embarrassed to perform, because they are given responsibility and enthusiasm so that they maximize the practice that can make them mentally strong enough to perform. Students will perform in cultural activities which can make student communication smoother in carrying out cultural activities. Therefore, this research aims to determine the relationship between cultural activities and student communication. The type of research used in this research is quantitative correlational research. Data collection techniques in this research used questionnaires and documentation. The population in this study was 331 class IX students with a sample of 25 class . The results of this research conducted at MTsN 1 Bukittinggi show that the relationship between cultural activities and student communication is 68% and 32% is influenced by other factors, so it can be concluded that there is a relationship between cultural activities and student communication at MTsN 1 Bukittinggi